2017
DOI: 10.1136/bjophthalmol-2017-310448
|View full text |Cite
|
Sign up to set email alerts
|

Six-year outcomes of antivascular endothelial growth factor monotherapy for polypoidal choroidal vasculopathy

Abstract: The results emphasised the efficacy of anti-VEGF therapy for preserving vision and the limitations of anti-VEGF therapy in that continuous treatment is required over an extended follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…Since long-term follow-up is difficult in ordinary clinical practice, the number of patients in each treatment group among various subtypes of PCV is relatively small, so that our results might need to be confirmed by further studies which include more subjects. Although we have examined the distribution of various treatment regimens among different subtypes of PCV, bias due to the small number of subjects seems to be unavoidable in such a study, which is similar to previous studies of long-term treatment for PCV [11][12][13][14][15][16]. Moreover, because of the retrospective nature of this study, long-term randomized clinical trials and prospective real-world studies are needed to investigate more effective treatment regimens for PCV according to imaging features.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Since long-term follow-up is difficult in ordinary clinical practice, the number of patients in each treatment group among various subtypes of PCV is relatively small, so that our results might need to be confirmed by further studies which include more subjects. Although we have examined the distribution of various treatment regimens among different subtypes of PCV, bias due to the small number of subjects seems to be unavoidable in such a study, which is similar to previous studies of long-term treatment for PCV [11][12][13][14][15][16]. Moreover, because of the retrospective nature of this study, long-term randomized clinical trials and prospective real-world studies are needed to investigate more effective treatment regimens for PCV according to imaging features.…”
Section: Discussionsupporting
confidence: 64%
“…An extensive study of the LAPTOP study reported a mean injection number of 14.8 for ranibizumab in the anti-VEGF monotherapy group over 5 years, in which the number of ranibizumab injection was 8.0 in 3 years after the LAPTOP study, while the number of aflibercept was 3.7 [14]. Another Japanese study reported a mean injection number of 18.2 for ranibizumab over 6 years [16]. Although conversive therapy of anti-VEGF agents might help reduce the injection number, other influential factors in real world should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous 6-year study, the 3-year VA after PRN anti-VEGF therapy for patients with PCV was similar to the baseline VA. 17 Similarly, a 3-year study assessing a PRN regimen for PCV reported that the post-treatment improvement in VA persisted until a year after treatment, with VA deterioration. 18 These findings are consistent with those of the present study.…”
Section: Discussionmentioning
confidence: 98%
“…Various clinical trials have demonstrated the efficacy of anti-VEGF monotherapy in PCV, and currently, it has become one of the first-line treatments for PCV [6,7]. Both ranibizumab and aflibercept have been used for the treatment of PCV.…”
Section: Introductionmentioning
confidence: 99%